(untitled) (Advances in Knowledge Representation, 2022)
The tree has been used as a key metaphor, since the Middle Ages, to depict knowledge representation systems. However, the contemporary socio-technical context demands considerations that admit other representations of the ways in which knowledge is produced, organized, and represented. In this sense, the purpose of this text is to reflect on arboreal images used historically as representational symbols of knowledge structures and, furthermore, to conjecture, within the scope of the transversal discussions that involve the plane of sociobiodiversity involved in the production of knowledge, about some of these representations used in different contexts and times. In the end, we arrive at the representation of the Rhizome proposed by G. Deleuze and F. Guatari, the Baniana tree by S. Ranganathan, and the Ruku tree, represented in the painting "The descent of the Jenipapo shaman from the kingdom of medicines", (2021), produced by the Makuxi indigenous artivist Jaider Esbell. The final considerations suggest that by broadening our understanding of the tree as a representation of relationships and not of dichotomies or hierarchies, we will be able to perceive, with more equity, the social, plural and cosmological arrangements of knowledge.